Peta riset modul ajar digital dalam pembelajaran membaca: Analisis bibliometrik dalam satu dekade - Nafisah, Yumna; Cahyani, Isah; Mulyati, Yeti; Sastromiharjo, Andoyo (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The advancement of digital technology has significantly transformed educational practices, particularly in the development of instructional modules for reading skills. This study aims to analyze developments related to the use of digital teaching modules in reading learning through a bibliometric approach. Data were extracted from the Dimensions database covering the years 2014–2024 and analyzed using VOSviewer software. The results reveal exponential growth in publications over the last three years, with research predominantly focused on content development, instructional effectiveness, digital accessibility, and educational platform integration. Bibliometric visualizations identified four thematic clusters: individual learning needs, pedagogical awareness, instructional design effectiveness, and institutional implementation. These findings indicate a paradigm shift from mere content provision to the optimization of adaptive and personalized digital media. Moreover, the analysis of authorship collaboration and citation patterns highlights limited inter-author networks and emphasizes the significance of influential publications in shaping digital literacy discourses. Themes that lead to needs dominate research on reading teaching modules that are in line with the educational needs of the 21st century.